Freedom for publishing, publishing for freedom : the Central and East European Publishing Project - Garton Ash, Timothy; Dahrendorf, Ralf, 1929-2009.; Davy, Richard; Winter, Elizabeth; Central and East European Publishing Project (Budapest : Central European University Press, 1995)
"The Oxford-based Central and East European Publishing Project was a remarkable initiative to support embattled Central and East European publishers and journals, and to punch holes through the cultural iron curtain by encouraging translations and a 'common market of the mind' between East and West. The nine years of its existence straddle the largest watershed in European history since 1945, and the Project's history - told here by some of its leading participants - illuminates the nature of the recent changes in Central and Eastern Europe." "In a vivid personal account, Timothy Garton Ash recalls the work of the Project, ranging from smuggling in subsidies to underground journals and samizdat publishers in the pre-1989 period to supporting high-quality translations and East-West workshops in the period after 1989. Also included are an Introduction in which Ralf Dahrendorf, Chairman of the Project, reflects on the importance of both publishing and foundations for a healthy civil society; an annotated catalogue of the Project's work, prepared by Elizabeth Winter; and a detailed and original report by Richard Davy on the state of publishing in the Czech Republic, Slovakia, Poland and Hungary, with suggestions for further Western help."--Jacket
Frontmatter -- Contents -- Editorial note -- Introduction -- The History of CEEPP -- Catalogue of Activity: Publications, Workshops and Fellowships supported by the Central and East European Publishing Project -- Publishing in the Visegrad countries in 1994: A report with suggestions for Western help -- 100 Books which have influenced Western public discourse since the Second World War
"100 books which have influenced western public discourse since the Second World War": pages 196-201
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Publishers and publishing -- Europe, Eastern; Publishers and publishing -- Europe, Central; Underground literature -- Publishing -- Europe, Eastern; Underground literature -- Publishing -- Europe, Central; Europe, Central -- Relations -- Europe, Western; Europe, Eastern -- Relations -- Europe, Western; Europe, Central -- Relations -- North America; Europe, Eastern -- Relations -- North America; Littérature clandestine -- Édition -- Europe de l'Est.; Littérature clandestine -- Édition -- Europe centrale; Europe de l'Est -- Relations -- Europe de l'Ouest.; Europe de l'Est -- Relations -- Amérique du Nord; Europe centrale -- Relations -- Europe de l'Ouest.; Europe centrale -- Relations -- Amérique du Nord; International relations; Publishers and publishing; Underground literature -- Publishing; Central Europe; Eastern Europe; Western Europe; North America; Uitgeven; Persvrijheid; Samizdat; Cold War, Czechia, East and West, Hungary, Late 20th century, Poland; Slovakia